SUSTAINABLE MANAGEMENT FROM THE INNOVATION PERSPECTIVE AND CIRCULAR ECONOMY: THE NATIVE CASE - Sehnem, Simone (2021)
This study analyzes the practices of circular economy and sustainable innovations that were adopted by Native - the largest producer of organic cane in Brazil. A documentary analysis was carried out and supported by two in-depth interviews. The results suggest that: (i) Native is a reference in the adoption of circular economy practices in terms of production, processing, industrialization and in the adoption of clean energies; (ii) sustainable innovations corroborate the prospect of transforming the production chain into an organic and sustainable chain; (iii) the launch of its own green seal will contribute to legitimize the brand in the institutional environment.